Development of Irrigation in India: A Spatio-temporal Study - Rajpriya; Rai, Vinay Kumar (National Geographical Journal of India, 2022)
Irrigation is one of the most important elements of agriculture, not from today but from the ancient past. From ancient timesthe need forwater for agriculture results in the discovery of irrigation methods. This paper is all about the evolution and development of irrigation in India from ancient to modern times based on topography and technology in India. The focus of this paper is to assessthe change inirrigation patterns in India inthe last decade and to analyze the role of planning commission in its development. Both positive and negative change has occurred with time. Some states show satisfactory progress while few states need special concern for irrigation development